UJI EFEKTIVITAS ANTHELMINTIK EKSTRAK RIMPANG BANGLE (Zingiber purpureum Roxb.) TERHADAP CACING Ascaridia galli SECARA IN VITRO - Yanthi Susanti; Indri Astuti; Ade Ari Dwi Astuti (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
The research was conducted to observe anthelmintic efficacy on rhizome extract bangle against Ascaridia galli by in vitro procedure. Experimental study was conducted, with samples rhizomes bangle powder and maceration method in three concentrations of 2%, 4% and 8%. The experimental animals used is Ascaridia galli with NaCl 0.9% as negative control and a pyrantel pamoate suspension as positive control with concentrations of 0.2%, 0.4% and 0.6%. The study was conducted in July 2014 at the Laboratory on IKIFA Academy of Pharmacy. The data analysis used is a probit analysis. Results of Research was rhizome extract bangle (Zingiber purpureum Roxb.) having as anthelmintic efficacy against Ascaridia galli with LC50 2.29% and LT50 in 4 hours 3 minutes 18 seconds